Comparative Analysis of Vital Statistics Among Four Provinces in Pakistan (Journal of Asian Development Studies, 2025)
Vital statistics are essential indicators and reflect a nation's health status and social well-being. It plays a crucial role in finding the demographic structure, health conditions, development level and planning needs. This research examines provincial disparities in Pakistan's key demographic indicators, including the crude birth rate, death rate, infant mortality rate, and life expectancy, utilising data from the Pakistan Demographic Survey (2020). Research findings show significant provincial disparities. Baluchistan exhibits the highest birth rate (29 per 1000) compared to Punjab's lowest rate (26 per 1000). Mortality patterns indicate that Punjab and Balochistan exhibit peak mortality rates of 7 per 1,000, while Khyber Pakhtunkhwa reports the lowest rate at 4 per 1,000. Sindh has the highest infant mortality rate (58/1000 births), whereas Khyber Pakhtunkhwa has a better outcome (53/1000). Life expectancy follows a comparable pattern of regional disparities, with Khyber Pakhtunkhwa leading (men: 66.4 years, women: 68 years) and Baluchistan trailing (men: 62.6 years, women: 64.3 years). These gaps reflect persistent differences in health infrastructure and development between provinces, which serve as key markers for targeted policy interventions.